Energy consumption measurement of C/C++ programs using clang tooling - Santos, Mário (2017)
The green computing has an important role in today's software technology. Either speaking about small IoT devices or large cloud servers, there is a generic requirement of minimizing energy consumption. For this purpose, we usually first have to identify which parts of the system is responsible for the critical energy peaks. In this paper we suggest a new method to measure the energy consumption based on Low Level Virtual Machine (LLVM)/Clang tooling. The method has been tested on 2 open source systems and the output is visualized via the well-known Kcachegrind tool.